PENGARUH KONTROL DIRI TERHADAP KECANDUAN GAME ONLINE PADA MAHASISWA SEMESTER VI PROGRAM STUDI FARMASI FAKULTAS FARMASI DAN ILMU KESEHATAN UNIVERSITAS SARI MUTIARA INDONESIA - Mora, Indo; Ramadhani, Sri; Tobing, Laksana; Laia, Mesradine (JURNAL PSYCHOMUTIARA, 2022)
Online game addiction is a dependence on something that is done repeatedly and is very difficult to stop which will have a negative impact by showing an attitude continuously by withdrawing. This research was conducted with the title of the effect of self-control on online game addiction in sixth students of the pharmacy study program, faculty of pharmacy and health sciences, University of Sari Mutiara Indonesia. This research was carried out in the Pharmacy Study Program, Faculty of Pharmacy and Health Sciences, University of Sari Mutiara Indonesia batch 2018 with a total sample of 69 people with a population of no more than 219 people. The sampling technique used was purpose sampling. The research was conducted using a quantitative approach. Data collection techniques using a questionnaire with a Likert scale model. The results showed that there was an effect of self-control on online game addiction with a high correlation categorization